Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Kez’s Bakery & Restaurant Batam - Gumilar, Gugung; Afrijal, Afrijal (Journal of Tourism Sciences, Technology and Industry, 2022)
Service quality is an important meaning for a service business to achieve  customer satisfaction. Good quality, friendly, fast and precise service will increase the number of customers.The formulation of the problem in this study is divided into two, namely whether service quality affects customer satisfaction at Kez's Bakery & Restaurant? And are there any service factors that affect customer satisfaction at Kez's Bakery  & Restaurant. The purpose of this study was to determine customer responses to  service quality at Kez's Bakery & Restaurant in Batam. To find out customer  responses to the satisfaction felt at Kez's Bakery & Restaurant in Batam. This research is included in quantitative research, the population in this study amounted to 3000 customers and the sampling was carried out by nonprobability sampling with purposive sampling method in order to obtain a sample of 97 customers. The data analysis method uses simple linear regression analysis, classical assumptions, hypothesis testing, then data processing uses the SPSS version 25 application. The t test results show that the service quality variable has a value based on the tcount> ttable test, namely 2.884 > 1.66105 and a significance value of 0.00 < 0.05, it can be concluded that Ho is rejected and Ha is accepted, which means that the variable service quality has a significant effect on customer satisfaction at Kez's Bakery & Restaurant in Batam.